American idyll : academic antielitism as cultural critique - Liu, Catherine (University of Iowa Press, 2011)
℗¡A trenchant critique of failure and opportunism across the political spectrum, American Idyll argues that social mobility, once a revered hallmark of American society, has ebbed, as higher education has become a mechanistic process for efficient sorting that has more to do with class formation than anything else. Academic freedom and aesthetic education are reserved for high-scoring, privileged students and vocational education is the only option for economically marginal ones. Throughout most of American history, antielitist sentiment was reserved for attacks against an entrenched aristocracy.